Correction: Carbon dioxide uptake from natural gas by binary ionic liquid–water mixtures. Issue 8 (3rd August 2015) - Anderson, Kris; Atkins, Martin P.; Estager, Julien; Kuah, Yongcheun; Ng, Shieling; Oliferenko, Alexander A.; Plechkova, Natalia V.; Puga, Alberto V.; Seddon, Kenneth R.; Wassell, David F.
<x xml:space="preserve">Abstract</x> Correction for 'Carbon dioxide uptake from natural gas by binary ionic liquid–water mixtures' by Kris Anderson et al., Green Chem., 2015, DOI: 10.1039/c5gc00720h.